Deskripsi Kesulitan Belajar Matematika Siswa pada Pokok Bahasan Bilangan Berpangkat di SMP Negeri 1 Biluhu - Verawati Tarsan Kadir; Nurwan Nurwan; Siti Zakiyah; Abdul Djabar Mohidin (Department of Mathematics, Universitas Negeri Gorontalo, 2022)
This article discusses student’s mathematics learning difficulties with the aim of describing student’s mathematics learning difficulties on the subject of power numbers. The method used in this research is descriptive which is carried out in class IX odd semester for the academic year 2021/2022. The subjects of this study were 20 students of class IX1of SMP Negeri 1 Biluhu. There were also three interview subjects who represented the high category, medium category, and low category. The instrument of this research is a difficult test in the form of an essay on the material of rank numbers. To see learning difficulties, 3 indicators are used, namely: (1) difficulties in learning principles, (2) difficulties in learning concepts, and (3) difficulties in learning operations. The results of this study indicate that the learning difficulties of class IX students of SMP country 1 Biluhu are in the moderate category.